An improved total synthesis of tunicamycin V - Katsuhiko Mitachi; David Mingle; Michio Kurosu (MethodsX, 2023)
The tunicamycins are important biochemical tools to study N-linked glycosylation and protein misfolding in cancer biochemistry fields. We reported a convergent synthesis of tunicamycin V with 21% overall yield from D-galactal. We have further optimized our original synthetic scheme by increasing the selectivity of azidonitration of the galactal derivative and developing a one-pot Büchner-Curtius-Schlotterbeck reaction. An improved synthetic scheme reported here enables the synthesis of tunicamycin V in 33% overall yield. In this article, we describe detailed procedures for a gram-scale synthesis of the key intermediate 12 and synthesizing 100 mg of tunicamycin V (1) from commercially available D-galctal-4,5-acetonide. All chemical steps have been repeated multiple times. • Highly selective azidonitration of N-(((3aR,4R,7aR)-2,2-dimethyl-3a,7a-dihydro-4H-[1,3]dioxolo[4,5-c]pyran-4-yl)methyl)acetamide (D-galctal-4,5-acetonide) to form 2-azido-2-deoxy-α/β-D-galactopyranoside derivatives. • Optimized Büchner-Curtius-Schlotterbeck (BCS) reaction procedure for the tunicamycin core structure. • Full detail on the 15-chemical step synthesis of tunicamycin V.